Synthesis, spectral characterization, DFT studies and biological activity of novel Ligand 1‐(2‐cyclohexyl thioethyl) piperidine and its complexes with group 12 metal chlorides. (25th March 2018) - Bhat, Muzzaffar A.; Lone, Shabir H.; Mir, Muzzaffar A.; Majid, Sheikh A.; Srivastava, Sanjay K.
Abstract : C6 H11 S ‐ Na + (generated insitu by reaction of NaOH with C6 H11 SH) on treatment with 1‐(2‐chloroethyl) piperidine hydrochloride under N2 atmosphere resulted in (1‐(2‐cyclohexyl thioethyl) piperidine) (L 1 ) as orange solid. It's complexes having the formula [ZnCl2 . L 1 ] (1 ), [CdCl2 . (L 1 )] (2 ) and [HgCl2 . L 1 ] (3 ) have been prepared.L 1 and its complexes1‐3 were characterized on the basis of physico‐chemical and spectral (FT‐IR, Mass, 1 H, 13 C and DEPT 135 o NMR) studies. Powder XRD diffraction pattern reveals the crystalline nature of L 1 and complex1 . Complexes1‐3 adopt distorted tetrahedral geometry showing bidentate mode of coordination through S and N. Using DFT‐based optimization of structures, the HOMO‐LUMO energy gaps and molecular electrostatic potential maps (EPM) of compound L 1 and complexes 1‐3 were theoretically calculated at the B3LYP/6‐311G (d, p) level of theory. HOMO‐LUMO energy gap was calculated which allowed the calculation of relative properties like chemical hardness, chemical inertness, chemical potential, nucleophilicity and electrophillicity index of the synthesized products. The experimentally obtained IR and NMR results showed a good correlation with those of the theoretical ones. LigandL 1 and complexes1‐3 display significant antibacterial and antifungal activity. Abstract : Formation ofL 1 is the first example of novel synthesis where 1‐(2‐chloro ethyl) piperidine hydrochloride and cyclohexyl thiol is used, which results in the formation of (S, N) hybrid donor ligand. LigandL 1 ligates through both N and S thus adopts bidentate mode of coordination in complexes1‐3 . Using DFT‐based optimization of structures, the HOMO‐LUMO energy gaps and molecular electrostatic potential maps (EPM) of compoundL 1 and complexes1, 2 and3 were theoretically calculated at the B3LYP/6‐311G (d, p) level of theory. LigandL 1 and complex 1‐3 display significant antibacterial and antifungal activity.